THE CENOZOIC DEFORMATION OF THE ALXA BLOCK IN CENTRAL ASIA-QUESTION ON THE NORTHEASTERN EXTENSION OF THE ALTYN TAGH FAULT IN CENOZOIC TIME - Zhang J.; Ma Z.; Li J.; Li Y. (My University, 2007)
Cenozoic deformation of the Alxa Block results directly from development of the northern Qinghai-Tibetan Plateau; however, a great volume of data show the deformation just occurred in the Middle and Late Miocene, and present activity of it is very weak. Our studies show the Altyn Tagh fault did not go through the Alxa block, on the contrary it went along the southern boundary of the Jinta-Huahai Basin, and linked with the fault to the southern Heli Mt. and Longshou Mt. During the Middle and Late Miocene, the important tectonic events occurring in the northern Qinghai-Tibetan Plateau compressed the western part of the corridor region, resulting in a tectonic change from NS trending to to EW trending in the Jinta-Huahai basin and an EW-trending faulting in the Beishan region which controls the Tertiary deposition. he right lateral movement of the southern margin of the Alxa Block resulted in an NS-trending Tertiary extensional structure in the northern and central parts of the block, which, along with the deposition in the Jinta-Huahai basin controlled by the Tertiary faults are very like basins developed in the lateral extrusion with strong foreland and weak limited boundaries. The authors believed that the regional "conjugate" fault system resulted from the nearly NS-trending compression of the Qinghai-Tibetan Plateau during Miocene and Pliocene in the Alxa and Mongolian regions. With brittle faults as the most active ones, new structures occurring in this area are subject to the old ones dominating the whole area, which were responsible for the formation of one conjugate fault system along the Altai Mountain in Mongolia. The faults in the Altyn Tagh and the southern margin of the Helishan-Longshoushan resulted in te formation of another conjugate fault system in the south of this area. The Beishan area and Jinta-Huahai basin are the convergent area of the two sets of faults, and characterized by distinct compression, which controls the Tertiary deposition and is responsible for the development of the Cenozoic Jinta-Huahai Basin. The Alxa Block bounded by these two sets of faults moved eastwards resulted in the development of Cenozoic compressive structures to the west of the Helan Mountain, and correspondingly, deformation occurred in the northeast and southwest margins. This model could explain the Cenozoic deformation occurring in and around the Alxa region and the relationship between the block and northern Qinghai-Tibetan Plateau reasonably.
Keywords: ALTYN TAGH FAULT; ALXA BLOCK; BAYANWULASHAN FAULT; CENOZOIC TIME; LIMITED LATERAL EXTRUSION; QINGHAI-TIBETAN PLATEAU; SOUTHERN LONGSHOU FAULT; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен